Gastroduodenal intussusception due to hypertrophic pyloric stenosis in a newborn: a case report - Bonny-Obro Rebecca; Aké Yapi Landry; Midekor-Gonebo Kokoé; Kouassi-Dria Amenan Kan; Ouattara Jean Jaures; Moh Ello Nicolas (Journal of Pediatric Surgery Case Reports, 2025)
Introduction: Intussusception is the most common cause of intestinal obstruction in infants but is an extremely rare condition in neonates. Intussusception may occur at any site in the gastrointestinal tract. Gastroduodenal intussusception is an unusual type of intussusception. Case report: An 18-day-old male neonate was referred to us due to postprandial non-bilious vomiting that began on day of life 5. He had no history of diarrhea, constipation, or fever. He was in poor general condition and had signs of dehydration. The abdomen was soft, non-tender, had no guarding and no palpable masses. Meconium-like stool was present in the diaper. Laboratory tests revealed moderate anemia and abnormal coagulation. The abdominal x-ray showed a lack of air in the gastrointestinal tract. We did an abdominal computerized tomography (CT) scan that showed a gastroduodenal intussusception. We took the patient to the operating room for an exploratory laparotomy. We found a gastroduodenal intussusception with a hypertrophic pylorus, a jejuno-jejunal intussusception, and an ileo-ileal intussusceptions. We reduced all the intussusceptions manually and did an extramucosal pyloromyotomy. The postoperative recovery was uneventful, and the patient was discharged on postoperative day 10. He is thriving well at five months of follow up. Conclusion: Gastroduodenal intussusception should be included in the differential diagnosis of newborns and young infants with gastric outlet obstruction.